AUTOMATIC CALCULATION OF BAND DIAGRAMS OF PHOTONIC CRYSTALS USING THE MULTIPLE MULTIPOLE METHOD - Smajic, Jasmin; Hafner, Christian; Erni, Daniel (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In the framework of photonic crystal’s band structure calculations, we present a novel way – based on several advanced techniques for searching and tracing eigenvalues with the multiple multipole program – to compute these diagrams automatically, efficiently, and with a high accuracy. Finally, we validate the results for some well known test cases.